GAMBARAN KONSUMSI MINUMAN MANIS, MAKAN GORENGAN, DEPRESI DAN AKTIVITAS FISIK PADA OBESITAS USIA DEWASA - Intan Nurul Azizah (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Background: Based on the results of Riskesdas in 2018, it can be seen that the prevalence of the adult population (>18 years) with overweight (BMI ≥ 25) is 8.9%. The prevalence of overweight and obesity in adults in East Java was 22.4%. The regency/city that has the highest prevalence of obesity nutritional status in East Java is Mojokerto City which is 44.18% and the Regency/City that has the lowest prevalence of obesity nutritional status is Sumenep Regency which is 18.23%. This study aims to determine the picture of the distribution and frequency of consumption of sugary drinks, eating fried foods, depression and physical activity in adult obesity in East Java based on secondary data from Riskesdas in 2018. Method: The design of this study uses descriptive quantitative research with a Secondary Data Analysis approach. Results: Consumption of sugary drinks, fried food consumption and depression are not related to one nutritional obesity in adolescence in East Java, while physical activity is related to the incidence of obesity nutritional status in adulthood in East Java. Conclusion: there is an increase in the proportion of nutritional status of obesity in adulthood which is closely related to physical activity. Less physical activity will result in fat accumulation because there is no burning process, which in the end the accumulation of fat makes a person obese. However, based on the results of cross-tabulation, there was no relationship between sweet consumption habits, fried eating habits, and depression with the proportion of obesity nutritional status in adulthood. Keywords: Sweet drink consumption, fried eating, depression, physical activity, obesity